Paradigm Istinbāṭ Verses of Faith from the Perspective of Muktazilah and Ahlusunah (Comparative Study of Az-Zamakshyarī and Az-Zuḥailī) - Holid, Abdul (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research proves that istinbāṭ is one of the Qur’anic sciences that developed since the birth of the science of exegesis. Istinbāṭ is not limited only to the legal verses that produce jurisprudence, but also includes other sciences such as creed, language, education, morals and others. This shows that the scope of istinbāṭ is wider and more than the exegesis and meanings taken directly from lafaẓ. This research uses qualitative research types of descriptive, analytical, and comparative models, namely analyzing data about the object under study according to its content that gives birth to conclusions, then continued by comparing between istinbāṭ az-Zamakhsyarī (d. 538 AH) and istinbāṭWahbah az-Zuḥailī (d. 1436 AH). From this research the author found several methods in issuing istinbāṭ, similarities and differences in istinbāṭ results between az-Zamakhsyarī (d. 538 AH) and az-Zuḥailī (d. 1436 AH) in terms of creed related to faith in Allah, angels, books, apostles and the last days.